CoOL [recurso electrónico] : Conservation On Line. Resources for conservation professionals. Stanford, Ca. : Preservation Department; Stanford University Libraries, [1993 - ]. [Consulta: 4 octubre 2004]. (Información, cultura y sociedad, 2004)
Reseña.